Vem ouvir o verso de teu cantador : amos, cantadores e toadas no Boi-Bumbá Caprichoso Belém/PA - Nascimento, Lanna Patrícia Marques do (2012)
This thesis aims to investigating the cantadores and the toadas in the Boi Bumbá, debating questions which put together around the construction and performance of amo s and cantador s role in the Boi Bumbá Caprichoso of Belém-PA city and exploring the extent of toadas its characteristics, functions, the uses that are made of theirs and the relations that establishes between them and the cantadores. The problematic of the research consisted on analysing what the amos, cantadores and toadas represent in the whole context of boi-bumbá plays in Belém, nowadays. Considering this perspective, I tried to identify on Boi Caprichoso the most meaningful expressions which were related to toadas and how the roles of amo and cantador were performed. Participative observation, ethnical research, open and semistructured interviews were used as research methods. The role performances on Boi Caprichoso plays an essential part on the playing realization, highlighting themselves as pivotal characters. These performances, characterized by the vocal presence, also highlighted the size that toadas occupy in the whole play, and pointed the way for an emerging model of presentation, in which both toada and cantador appear as central figures